2004
DOI: 10.1038/sj.bmt.1704582
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Vα24+ NKT cells after hematopoietic stem cell transplantation

Abstract: Summary:Human Va24 þ natural killer T (NKT) cells have an invariant T-cell receptor-a chain and are activated in a CD1d-restricted manner. Va24 þ NKT cells are thought to regulate immune responses and to play important roles in the induction of allograft tolerance. In this report, we analyzed the recovery of Va24 þ NKT cells after hematopoietic stem cell transplantation and its correlation with graft-versus-host disease (GVHD). Patients who received a dose-reduced conditioning regimen, antithymocyte globulin-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 35 publications
4
48
0
Order By: Relevance
“…Only two studies so far have addressed iNKT cell reconstitution after allogeneic HSCT and demonstrated that iNKT cells emerged and reconstituted to normal values before T cells. The possible correlation between iNKT cell reconstitution and remission was not addressed, although one study suggested that a low number of iNKT cells could be related to the development of GVHD (36). Both studies were performed in adult patients receiving either T cell-replete HLA-matched allogeneic HSC or umbilical cord blood (36,37), and thus required posttransplantation treatment with immune-suppressive drugs to prevent GVHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies so far have addressed iNKT cell reconstitution after allogeneic HSCT and demonstrated that iNKT cells emerged and reconstituted to normal values before T cells. The possible correlation between iNKT cell reconstitution and remission was not addressed, although one study suggested that a low number of iNKT cells could be related to the development of GVHD (36). Both studies were performed in adult patients receiving either T cell-replete HLA-matched allogeneic HSC or umbilical cord blood (36,37), and thus required posttransplantation treatment with immune-suppressive drugs to prevent GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…The possible correlation between iNKT cell reconstitution and remission was not addressed, although one study suggested that a low number of iNKT cells could be related to the development of GVHD (36). Both studies were performed in adult patients receiving either T cell-replete HLA-matched allogeneic HSC or umbilical cord blood (36,37), and thus required posttransplantation treatment with immune-suppressive drugs to prevent GVHD. This faster iNKT cell reconstitution dynamics could depend, at least in patients given HLA-matched HSC, on the adoptive transfer of donor-derived mature lymphocytes present in the graft and/or the different transplantation protocols used in these studies, as compared with our approach of T cell depletion of the graft.…”
Section: Discussionmentioning
confidence: 99%
“…3 Human iNKT cells have been implicated in the regulation of autoimmune responses in various diseases [4][5][6] (ie, type 1 diabetes, 7-9 multiple sclerosis, 10,11 and others 12,13 ) and graft-versus-host disease (GVHD). 14 Patients with autoimmune diseases or GVHD typically have reduced frequency of iNKT cells [7][8][9][10][11][12][13][14] with reduced capacity to produce Th2 cytokines, including IL-4 and IL-10. [7][8][9][10][11] The secretion of Th2 cytokines polarizes naive T cells toward a Th2 response and is thought to shift the balance from a pathogenic Th1 toward a protective Th2 response in Th1-dominant autoimmunity.…”
mentioning
confidence: 99%
“…There is only one study 82 that has examined the frequencies of total as well as CD4 + and CD4 − iNKTs in donor PBSC grafts. In a previous study, 80 there was a significant difference in the number of reconstituted iNKTs in patients who received BMT and PBSC. The only variable associated with the number of iNKTs was the stem cell source (peripheral blood or BM).…”
Section: Role Of Human Inkts In Clinical Gvhdmentioning
confidence: 99%
“…79 Second, both CD4 + and CD4 − subsets of iNKTs (Table 1) are reduced in patients with acute GvHD. 80 Third, enhanced iNKT reconstitution post transplantation has been shown to be a predictive factor for an improved overall survival associated with reduction in GvHD without abrogation of the GvL effect. 81 Fourth, lower numbers of CD4 − iNKTs in the donor graft is associated with clinically significant GvHD in patients undergoing HLA-identical allogeneic HSCT.…”
Section: Role Of Human Inkts In Clinical Gvhdmentioning
confidence: 99%